Increase in glutamate/glutamine concentration in the medial prefrontal cortex during mental imagery: A combined functional mrs and fMRI study. Issue 8 (9th June 2015) - Huang, Zirui; Davis Iv, Henry (Hap); Yue, Qiang; Wiebking, Christine; Duncan, Niall W.; Zhang, Jianfeng; Wagner, Nils‐Frederic; Wolff, Annemarie; Northoff, Georg
Abstract Recent functional magnetic resonance spectroscopy (fMRS) studies have shown changes in glutamate/glutamine (Glx) concentrations between resting‐state and active‐task conditions. However, the types of task used have been limited to sensory paradigms, and the regions from which Glx concentrations have been measured limited to sensory ones. This leaves open the question as to whether the same effect can be seen in higher‐order brain regions during cognitive tasks. Cortical midline structures, especially the medial prefrontal cortex (MPFC), have been suggested to be involved in various such cognitive tasks. We, therefore set out to use fMRS to investigate the dynamics of Glx concentrations in the MPFC between resting‐state and mental imagery task conditions. The auditory cortex was used as a control region. In addition, functional magnetic resonance imaging was used to explore task‐related neural activity changes. The mental imagery task consisted of imagining swimming and was applied to a large sample of healthy participants (n = 46). The participants were all competitive swimmers, ensuring proficiency in mental‐swimming. Glx concentrations in the MPFC increased during the imagery task, as compared to resting‐state periods preceding and following the task. These increases mirror BOLD activity changes in the same region during the task. No changes in either Glx concentrations or BOLD activity were seen in the auditory cortex. These findings contribute to our understanding of the biochemical basis of generating or manipulating mental representations and the MPFC's role in this. Hum Brain Mapp 36:3204–3212, 2015. © 2015 Wiley Periodicals, Inc.